The Effect of Coagulants Variations in the Coagulation Unit on the Efficiency of Raw Water Turbidity Removal Sedimentation Unit Continuous Discharges Flow (CDF) as a New Method - Ridwan, Ridwan; Afrianita, Reri; Danir, Resi Meilinta Danir (Andalasian International Journal of Applied Science, Engineering and Technology, 2021)
Variations in the type of coagulant resulted in different floc characteristics. The sedimentation unit with continuous discharges flow or (CDF) method is a sedimentation unit that applies the leaking tank phenomenon, so it is possible that it will affect the condition of the floc that has been formed and in the end can affect the efficiency of turbidity removal. This study was to determine the effect of the type of coagulant in the coagulation unit on the removal of raw water turbidity in the sedimentation unit using the CDF method with a 6% discharge ratio to the product discharge. The raw water used is Sungai Batang Kuranji water with a turbidity of 27.63 NTU. The experimental reactor consisted of a coagulation-flocculation unit and a sedimentation unit with various coagulants being Poly Aluminum Chloride (PAC), Ferric Chloride, and Alum. The results showed that the efficiency of removing turbidity from the Sungai Batang Kuranji by PAC coagulant was 90.12%, Ferric Chloride 86.99%, and Alum 81.72%. The Spearman correlation value of the coagulant variable on the efficiency of the removal of turbidity is 0.948, indicating a unidirectional effect between the two variables. The addition of 6% CDF flow in the settling zone did not break the floc because the flow formed was still laminar.